Through the eyes of a researcher: a school’s literacy project - Torres Jaramillo, Claudia (Colombian Applied Linguistics Journal, 2003)
Research and reflection are two key aspects for teachers’ growth and development. This article is a final report of a research study which aims at describing the process lived by the English coordinator and a group of high school teachers from various disciplines which was sponsored by el Instituto para la Investigación y el Desarrollo Pedagógico - IDEP (one of the most serious institutions that support educational research in Colombia). The group of researchers wanted to systematically and critically observe and analyze the reading and writing pedagogical practices held at school in order to construct collectively a better understanding of these two fundamental processes in teaching. By narrating the research experience through the eyes of one of its participants (the English coordinator), one can see that carrying out research can be a complex but very gratifying experience that can have an impact on one’s professional growth and development.